2018
DOI: 10.1152/japplphysiol.00005.2018
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and autonomic changes in adult cancer patients receiving anticancer chemotherapy

Abstract: Chemotherapy is associated with acute and long-term cardiotoxicity. To date, risk assessment has primarily focused on the heart; however, recent findings suggest that vascular and autonomic function may also be compromised. Whether this occurs during chemotherapy treatment remains unknown. Therefore, the present study evaluated carotid artery stiffness, cardiovagal baroreflex sensitivity (cBRS), and heart rate variability (HRV) in cancer patients currently being treated with adjuvant chemotherapy. Eleven curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Given that current standard chemotherapy practice often involves combination or sequential chemotherapy regimens with multiple agents (11), it was appropriate to include all patients in the study. The inclusion of this normal, but diverse, group of chemotherapy agents is consistent with previous investigations by our laboratory and others aimed at evaluating the adverse changes in arterial stiffness and vascular control with anticancer chemotherapy (8,18,23,27,46). Since the timing between cancer diagnosis, possible surgery, and onset of chemotherapy is often limited, a cross-sectional study design was utilized.…”
Section: Participantsmentioning
confidence: 94%
“…Given that current standard chemotherapy practice often involves combination or sequential chemotherapy regimens with multiple agents (11), it was appropriate to include all patients in the study. The inclusion of this normal, but diverse, group of chemotherapy agents is consistent with previous investigations by our laboratory and others aimed at evaluating the adverse changes in arterial stiffness and vascular control with anticancer chemotherapy (8,18,23,27,46). Since the timing between cancer diagnosis, possible surgery, and onset of chemotherapy is often limited, a cross-sectional study design was utilized.…”
Section: Participantsmentioning
confidence: 94%
“…Middle-aged patients also appear to undergo arterial stiffening in response to treatment with anthracyclines. For example, Frye et al 44 recently demonstrated ∼20% greater carotid artery β stiffness in middle-aged (mean age: 56 years) patients receiving anthracycline chemotherapy relative to age-matched controls. In another study, Chaosuwannakit et al 45 showed that 4 months following completion of anthracycline treatment in middle-aged patients, there was a three-fold increase in carotid-femoral PWV from baseline relative to controls.…”
Section: Middle-aged Adults Receiving Anthracycline Chemotherapymentioning
confidence: 99%
“…Moreover, these studies have suggested that the upregulation of the SNS and/or PNS may also promote tumor growth and metastasis [ 18 , 19 ]. More importantly, studies have observed larger decrements in HRV among cancer patients in the advanced stages which were associated with poorer prognosis, increased mortality risk, and decreased survivorship following surgical operations and pharmaceutical interventions [ 13 , 20 , 21 ]. While scientific evidence reliably shows depressed HRV patterns among patients diagnosed with cancer, much less is known about whether specific cancer locations such as gastrointestinal and breast cancer can elicit varying HRV patterns at different stages.…”
Section: Introductionmentioning
confidence: 99%